Hemp in Veterinary Medicine: From Feed to Drug - della Rocca, Giorgia; Di Salvo, Alessandra (Frontiers in Veterinary Science, 2020)
Hemp (Cannabis sativa) is an angiosperm plant belonging to the Cannabaceae family. Its cultivation dates back to centuries. It has always been cultivated due to the possibility of exploiting almost all the parts of the plant: paper, fabrics, ropes, bio-compounds with excellent insulating capacity, fuel, biodegradable plastic, antibacterial detergents, as well as food products, such as flour, oils, seeds, herbal teas and beer are indeed obtained from hemp. Hemp flowers have also always been used for their curative effects, as well as for recreational purposes due to their psychotropic effects. Cannabis contains almost 500 chemical compounds, such as phytocannabinoids, terpenes, flavonoids, amino acids, fatty acids, vitamins, macro- and micro-elements, among others. When utilized as a food source, hemp shows excellent nutritional and health-promoting (nutraceutical) properties, mainly due to the high content in polyunsaturated fatty acids (especially those belonging to the -3 series), as well as in phenolic compounds, which seem effective in the prevention of common diseases such as gastrointestinal disorders, neurodegenerative diseases, cancer, and others. Moreover, hemp oil and other oils (i.e. olive oil and medium chain triglyceride – MCT - oil) enriched in CBD, as well as extracts from hemp dried flowers (Cannabis extracts), are authorized in some Countries for therapeutic purposes as second choice approach (when conventional therapies have failed) for a certain number of clinical conditions such as pain and inflammation, epilepsy, anxiety disorders, nausea, emesis and anorexia, among others. The present review will synthetize the beneficial properties of hemp and hemp derivatives in animal nutrition and therapeutics.